Does the rise of China present a threat to the interests of the United States? - Fadhila Inas Pratiwi; Dini Putri Saraswati; M. Muttaqien (Masyarakat, Kebudayaan dan Politik, 2018)
The rise of China can be perceived either as a threat or as an opportunity to and for the US, mostly depending on US grand foreign policy interests and its related strategies. If the US feels comfortable living in a multipolar world in which it is considered to be an equal among the major powers, China is more likely to be perceived as a partner. However, if the goal of US foreign policy is to strengthen its position as the sole superpower or even as a hyper-power, and does not choose to recognise other major countries, then the rise of China will be perceived as a threat. Based on this underlying assumption, this article seeks to examine the exact interests of the US: Is it threatened by the rise of China or is it not? This article starts by explaining the grand theories and relating it to the research question. The next explanation examines the economic ties between the two countries. The final consideration is the possibility of military conﬂict given several recent occurrences, such as the Taiwan and South China Sea (SCS) dispute. This article concludes that the rise of China will threaten the interests of the US. However, it will not necessarily lead to war between them.